Genetic, protein and pharmacological modulation of human alpha7 nicotinic receptors - Bouzat, Cecilia Beatriz (2019)
The α7 nicotinic acetylcholine receptor is a pentameric ligand gated ion channel. It is widely expressed in the central nervous system where it is involved in cognition, attention, and memory. It is also expressed in many non-neuronal cells and its activation has anti-inflammatory and neuroprotective roles. Enhancement of α7 activity is emerging as a therapeutic strategy for cognitive, neurodegenerative and inflammatory disorders. We have focused on understanding α7 function and its different mechanisms of modulation associated to physiological, pathological and therapeutic situations. By single-channel recordings we determined that positive allosteric modulators (PAMs) enhance α7 activation by increasing open-channel lifetime and inducing prolonged activation episodes, and we also identified novel PAMs. Although α7 has been considered the homomeric member of the family, heteromeric α7β2 receptors have been detected in human brain. We generated α7β2 receptors with different stoichiometries and determined how the β2 subunit modifies α7 kinetics and its allosteric modulation. This information is required to decipher the role of α7β2 receptors in native cells. In humans, there is a truncated α7 subunit (dupα7) that lacks part of the ACh-binding site and results from partial duplication of the α7 gene. We demonstrated that dupα7 acts as a negative modulator and can assemble with α7 into functional heteromeric receptors. Deciphering the molecular basis underlying α7 function has implications for the design of novel therapeutic compounds as well as for clarifying its pleiotropic actions.